Risk factors for bleeding after dental extractions in patients receiving antithrombotic drugs - A case control study - Jinxia Huang; Jie Liu; Haitao Shi; Jun Wu; Jiyuan Liu; Jian Pan (Elsevier, 2022)
Background/purpose: Patients receiving antithrombotic drugs are more likely to suffer bleeding after tooth extraction and multiple factors are related to it. The aim of this study was to investigate the incidence of bleeding and risk factors for bleeding after dental extractions in patients receiving antithrombotic drugs. Materials and methods: This retrospective case control study included patients receiving oral antithrombotic drugs or not. Tooth extractions were conducted under ECG monitoring and local hemostatic measures were performed. Risk factors for postoperative hemorrhage after tooth extraction were evaluated using univariate and multivariate analyses. Results: Bleeding events were reported in 27 (27%) patients receiving antithrombotic drugs and 9 (9%) patients who didn't use antithrombotic drugs, the difference between which was significant (p < 0.01). Univariate analyses showed that age (OR = 2.717, p = 0.028), oral hygiene (OR = 4.110, p = 0.043), inferior nerve block (OR = 4.285, p = 0.038) and number of extracted tooth (OR = 4.758, p = 0.029) were significantly correlate with bleeding incidence. Multivariate analysis revealed that age (OR = 2.824, p = 0.036) and number of extracted tooth (OR = 5.268, p = 0.016) were significant risk factors for postextraction bleeding. Conclusion: The results suggest that there is higher incidence of postextraction bleeding in patients receiving antithrombotic drugs compared to patients who don't. Age (>75 years), oral hygiene, inferior nerve block and number of extracted tooth may be related to bleeding after tooth extraction.